Online Accommodation Management System for UTHM Students - Song Zhi Wei, Jocelyn; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2025)
The Online Accommodation Management System for UTHM students is built to address inefficiencies in the manual registration process. The new system allows students to register, view roommates, manage profiles, and handle online bookings. By eliminating queues and introducing key collection through time slots, the system reduces administrative workload, prevents document loss, and saves space. Developed with PHP and MySQL using the iterative waterfall model, it streamlines operations, ensuring data accuracy and a better student and staff experience. This system aims to improve the overall efficiency of the hostel management process.